1999
DOI: 10.1101/gad.13.11.1453
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of male development in Caenorhabditis elegans by a protein-protein interaction between TRA-2A and FEM-3

Abstract: The tra-2 gene of the nematode Caenorhabditis elegans encodes a predicted membrane protein, TRA-2A, that promotes XX hermaphrodite development. Genetic analysis suggests that tra-2 is a negative regulator of three genes that are required for male development: fem-1, fem-2, and fem-3. We report that the carboxy-terminal region of TRA-2A interacts specifically with FEM-3 in the yeast two-hybrid system and in vitro. Consistent with the idea that FEM-3 is a target of negative regulation, we find that excess FEM-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 47 publications
5
95
0
Order By: Relevance
“…Somatic FEM-3 expression has not been shown previously (34) but is supported by genetic data: Somatic feminization of tra-1(gf) males is suppressed by gain-of-function mutations in the fem-3 3′ UTR that do not affect fem-3 transcript levels (26). Thus, FEM-3 activity is regulated through at least three separate means: The transmembrane receptor protein TRA-2 represses FEM-3 protein activity via physical interaction (35), fem-3 mRNA is negatively regulated via the 3′ UTR (36), and we find that fem-3 also is transcriptionally repressed by TRA-1. Therefore fem-3 appears to be an important node for control of the sex determination pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Somatic FEM-3 expression has not been shown previously (34) but is supported by genetic data: Somatic feminization of tra-1(gf) males is suppressed by gain-of-function mutations in the fem-3 3′ UTR that do not affect fem-3 transcript levels (26). Thus, FEM-3 activity is regulated through at least three separate means: The transmembrane receptor protein TRA-2 represses FEM-3 protein activity via physical interaction (35), fem-3 mRNA is negatively regulated via the 3′ UTR (36), and we find that fem-3 also is transcriptionally repressed by TRA-1. Therefore fem-3 appears to be an important node for control of the sex determination pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Our experiments presented here show that mir-35-41 target multiple components of cell proliferation control pathways, to ensure correct cell numbers in the intestine and gonad. By qRT-PCR, we also found that mir-35-41 directly or indirectly regulate genes such as fem-2, fem-3 and xol-1, which all encode proteins required in the somatic sex determination pathway [62][63][64][65] (our unpublished data). It remains to be seen elusive if such a regulatory scheme of a miR-NA family applies to all multi-cell organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In XX animals, the her-1 gene, which encodes a secreted protein, is not expressed (2). The lack of her-1 expression in XX animals permits the activation of the transmembrane protein TRA-2, which blocks the functions of FEM-1 (a novel protein) (3), FEM-2 (a type 2C protein phosphatase) (4,5), and FEM-3 (an ankyrin-repeat protein) (6), possibly by interacting directly with FEM-3 (7). This block leads to the activation of the Zn-finger DNA-binding protein TRA-1 (8).…”
mentioning
confidence: 99%